Problems of Legal Competency of Innovative Infrastructure Subject within the Format of Assistance to Entrepreneurship in Forestry Legal Relations: Expediency of European Union Experience Implementation - Liubchych, Anna; Savchuk, Olena; Berkutova, Tetyana (European Journal of Sustainable Development, 2019)
At present there is observed a change in world economy and development of evolving market relations in society alongside the transition of economy to innovative mode of development. Innovation infrastructure subjects act as obligatory participants of innovative relationships. According to the Law of Ukraine “On Investment Activity”, art.5, the subjects of innovative activities are physical and (or) juridical persons of Ukraine, physical and (or) juridical persons of foreign states, persons without citizenship, associations of the mentioned persons who conduct innovative activities in Ukraine and (or) involve property and intellectual values, invest their own or borrowed finances for realizing innovative projects in Ukraine[1]. Entrepreneurship is considered a leading component in the processes of stable development of forest resources under conditions of market liberalization of utilizing natural resources and forest in the EU. Attracting investments to this sphere is to be based on recognition of all kinds of forestry operations as business activities with corresponding remuneration of these activities’ results. Besides, improvement of financial mechanism is an integral condition of ecologically balanced use of forestry, because at present it acts as an impeding factor of efficient development of forestry into the EU countries. Investment provision improvement is possible under favorable credit and financial preconditions for financing the processes of restoring forest resources potential. It is possible to improve investment attractiveness of forestry business, especially for foreign investors, on the premise of real implementation of elements of modern ecological management into business practices. Keywords: EU countries, foreign experience, entrepreneurship, forests, forestry legal relations, innovations, innovative activities, innovative infrastructure, subjects. [1] Law of Ukraine “On investment activities”. The Verkhovna Rada Bulletin, 2002, no 36, p. 266.